Analisis Komparatif Efektivitas Teknik Bakar dalam Mixing Foundation terhadap Coverage dan Durabilitas Rias Wajah Cikatri - Vanesa Monica; Raisa Marchella Maulida; Nathania Citta Pribawanto; Elina Sudi Dwi Ariyani; Zakiyya Dewi Salsabila (Lembaga Pengembangan Kinerja Dosen, 2026)
Corrective makeup application on acne-prone skin with scarring presents complex technical challenges related to product adhesion and discontinuity in skin texture. This condition has been clinically proven to impact individuals' quality of life and increase social anxiety. Conventional application techniques often fail to provide maximum coverage and long-term durability on skin with sebum hypersecretion. As an innovative solution, practitioners have developed a thermal modification method or burning technique in the product mixing process. This study aims to comparatively analyze the effectiveness of the burning method of foundation mixing compared to the manual technique on coverage, texture smoothness, and durability of makeup on scarring skin through a Systematic Literature Review (SLR) design. This study analyzed 17 experimental research articles that met the inclusion criteria from the publication range of 2020–2025. The findings showed that the burning technique was significantly superior with an increase in durability of up to 89% on oily skin, far exceeding the manual technique which only achieved 64%. The coverage score reached 3.85/4.00 and texture smoothness reached 83%. Physicochemical analysis indicates that heating changes the rheological structure through the evaporation of volatile solvents, increasing the viscosity and density of the pigments, thus creating a more sebum-resistant film. The burning technique is validated as an effective method for professional cosmetic camouflage and is recommended for integration into cosmetology education curricula.